Response of green lettuce (Lactuca sativa L.) by granting of biochar types and dosage of NPK fertilizer - S Sugiyarto; Refa Firgiyanto; Diablo Cardilac; Abdurrahman Salim (Universitas Trunojoyo Madura, 2023)
This study aims to determine the effect of giving the type of biochar, the effect of the dose of NPK fertilizer, and knowing the interaction of the type of biochar and the dose of NPK fertilizer on the growth and production of green lettuce. This research was conducted in May 2020 at the Screen House of the Jember State Polytechnic with an altitude of ±89 meters above sea level. The method used is a factorial Completely Randomized Design (CRD). The first factor is the type of biochar which consists of 3 levels, namely B0 (without biochar), B1 (rice husk charcoal biochar), B2 (coconut shell biochar). The second factor is the dose of NPK fertilizer which consists of N0 (NPK 0.501 g), N1 (NPK 1.02 g), N2 (NPK 2.04 g). Parameters observed were number of leaves (strands), plant height (cm), leaf area (cm2), canopy wet weight (gr), canopy dry weight (gr), root wet weight (gr), root dry weight (gr), and total chlorophyll content. Based on the results of the recapitulation analysis of the F test, the application of biochar fertilizer on the growth and production of green lettuce gave a very significant effect on the chlorophyll amount of treatment B2 (coconut shell biochar), the application of NPK fertilizer got significantly different results in the treatment of plant height 3 WAP, number of leaves 3 MST and leaf area with the highest yields were 29.33 cm (N3), 11.56 strands (N3) and 116.56 cm2 (N3). There was no interaction between biochar treatment and the position of NPK fertilizer.